Enhanced matrix-based error correction coding techniques for embedded memories - Jammula Shivani; Mandadi Shankar Teja Teja; Manickaraj Vinodhini (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
Memories play a very important role in computing systems due to the continuous advancements in technology. They are used to store data that is used for proper system operations. Memory architectures that are more intricately designed are more prone to radiation-induced errors such as single bit upsets (SBU) and multiple bit upsets (MBU). Error correction codes (ECC) are used to recover the corrupted data that are stored in memories. H-matrix-based ECC is the commonly used ECC for memories. On the other side, the correction masking (CM) technique was added to ECC to mask the correctable error patterns. CM technique protects the error-free bits while correcting erroneous bits. In this paper, optimized H-matrices are presented. These matrices are used to design an ECC with the CM technique to correct 2-bit to 7-bit adjacent errors. The result shows there is a reduction in the power of 2, 3, and 4 adjacent bit errors by 19.009%, 4.615%, and 27.934% respectively.